Coverage and compliance of mass drug administration for elimination of lymphatic filariasis in Khammam district - Alwala, Rajeshwar Rao; Bolla, Chandrasekhar Reddy; Dudala, Shankar Reddy; Raju, Y. Pravin; Mondal, Raston; Kumar, B. P. Ravi (International Journal Of Community Medicine And Public Health, 2018)
Background: Lymphatic filariasis (LF) is an important public health and socio-economic problem in the world and it was identified as one of the six diseases, which could be targeted for elimination /eradication. Annual mass drug administration of DEC with selective vector control could result in the effective elimination of infection by interruption of transmission. The present study aimed to find the coverage and compliance of mass drug administration (MDA) of diethyl-carbamazine (DEC) for elimination of lymphatic filariasis (LF) in Khammam district in November 2009. Methods: Cross-sectional, population-based, house-to-house survey was conducted after the round of MDA with DEC. Multi-stage systematic sampling method was used and four clusters were selected with 30 houses in each. A pretested questionnaire was used to interview the study participants. The data collected was analyzed and coverage rate, compliance rate and effective coverage rate were calculated. Results: The coverage rate was 65.54% with variation across different areas. The compliance with drug ingestion was 71.14%. The effective coverage (46.63%) was much below the target (85%) which has to be targeted by intensive information, education and communication (IEC). Side effects of DEC were minimum, transient and drug-specific. Conclusions: The coverage, compliance, and effective coverage rates were found to be lower than the target, which need to be intensified by extensive IEC.